Spinal Tap II : the end continues [videorecording (DVD)] - Reiner, Rob; Reiner, Rob; Guest, Christopher; Guest, Christopher; McKean, Michael; McKean, Michael; Shearer, Harry, 1943-; Shearer, Harry, 1943-; Else, Lincoln; Bott, Lauren (Decal ; Bleecker Street, 2025)
"Forty-one years after This is Spinal Tap, now estranged bandmates David St. Hubbins, Nigel Tufnel, & Derek Smalls reunite for one final concert captured once again by documentarian Marty Di Bergi. Joined by music royalty Paul McCartney and Elton John, Spinal Tap wrestles with their checkered past to put on a concert that they hope will solidify their place in the pantheon of rock 'n' roll."--